What do professional science teachers need today? A learning model integrating reflection and collaboration principles - Hamdani, Hamdani; Saefi, Muhammad; Marlina, Reni; Sudrajat, Ahmad Kamal; Pamungkas, Rahmania (Universitas Islam Negeri Raden Intan Lampung, 2025)
Collaboration and reflection on learning implementation should be clear and sustainable. This study aims to introduce a model that integrates the principles of collaboration and reflection. The research method is quantitative descriptive. The participants involved were preservice science teachers who were taking micro-teaching courses. The research implementation lasted for 4 months. The first month, a Focus Group Discussion (FGD) was conducted with school partners. The next month was to design a learning model by integrating collaborative and reflective principles. The third month is to measure the validity of the stages of the model. The last month was the implementation of the learning model in micro-teaching courses. Each learning implementation was recorded and uploaded on the web. The learning model with collaborative and reflective principles consists of 4 stages: plan, simulation, implementation, and reflection. The result states that the learning model is valid and reliable. This model is valid in content and constructs, fulfilling development needs and model novelty. This study implies an enhancement of science education through micro-teaching, offering strategic directions for the pedagogy development of the preservice teachers.